2011
DOI: 10.1007/bf03337764
|View full text |Cite
|
Sign up to set email alerts
|

Increased intra-individual variability in stride length and reaction time in recurrent older fallers

Abstract: Older recurrent fallers are characterized by increased within-task variability in reaction time and stride length while dual-tasking. In addition, variability in performance is a more sensitive measure in discrimination of recurrent falls than mean performance itself, suggesting deterioration in neurocognitive regulation mechanisms as part of the causal pathway for recurrent falls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…Of these, 13 analyzed a single group of elderly individuals [25][26][27][28][29][30][31][32][33][34][35][36][37] and 15 compared groups of elderly individuals with different characteristics. 5,6,[16][17][18][19][20][21][38][39][40][41][42][43][44] Charts 1 and 2 contain the details of the studies included in this review, as well as the details of the samples, instruments, tasks and spatial and temporal parameters of gait in each study. Step time; variability of the step …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these, 13 analyzed a single group of elderly individuals [25][26][27][28][29][30][31][32][33][34][35][36][37] and 15 compared groups of elderly individuals with different characteristics. 5,6,[16][17][18][19][20][21][38][39][40][41][42][43][44] Charts 1 and 2 contain the details of the studies included in this review, as well as the details of the samples, instruments, tasks and spatial and temporal parameters of gait in each study. Step time; variability of the step …”
Section: Resultsmentioning
confidence: 99%
“…The other four studies used a DT with an arithmetic CT, a verbal fluency CT and an executive function CT and found no significant effect on gait speed. 20,21,38,41 …”
Section: Speedmentioning
confidence: 99%
See 1 more Smart Citation
“…From a clinical point of view, dual-task paradigms have been used to distinguish fallers from non-fallers among AD patients. For example, Reelick et al (2011) showed that only stride length variability discriminate significantly between the faller groups in the dual-task, and not the single-task, condition. Furthermore, if clinicians are seeking further information on attention and executive functions of their patients, dual-task gait paradigms might be of value to explore the attentional requirement of balance during locomotion (Amboni et al 2013;Menant et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Although the relationship between COP variability during gait and balance or fall risk has not been studied in the scientific literature yet, it could be a potential variable for dynamic balance assessment. It was showed that in subjects with fall history, gait variability in temporal-spatial variables such as stride length (Reelick et al, 2011;Taylor, Delbaere, Mikolaizak, Lord, & Close, 2013), stride time (Hausdorff, Edelberg, Mitchell, Goldberger, & Wie, 1997;Miyoshi, Kinugasa, Urushihata, & Soma, 2011), swing time (Taylor et al, 2013) or minimum foot clearance (Barrett, Mills, & Begg, 2010) and kinematic variables (Barak et al, 2006) is increased.…”
Section: Introductionmentioning
confidence: 99%